Świat zmieścić w objawieniu chwili: „The Epiphanies” Jamesa Joyce’a w tłumaczeniowym kalejdoskopie - Wieczorkiewicz (Michalska), Aleksandra (Wydawnictwo Korporacja ha!art, 2013)
The article focuses on the cycle of short pieces of prose which are classified among the early works of James Joyce. The Epiphanies are a kind of artistic transcript of reality by which the author was surrounded and which was speaking to him through symbols, gestures, behaviour, appearances, phenomena and, most of all, through the alchemy of words and human language. Joyce’s epiphanies – poetic pieces in the form of sketch or description, records of memorable phase of mind itself or short dramatic dialogues with author’s stage directions, sudden manifestations of vulgarity of speech or gesture – started the literary career of epiphany. As a separate entirety, a separate piece of work collected and rewritten by Joyce himself scrupulously on separate sheets of paper, some of the epiphanies were also woven by the author into his narrations and short stories. The epiphanies, slightly changed or in their intact form, became an integral part of Joyce’s novels: Stephen Hero, Portrait of the Artist as a Young Man and Ulysses. The article analyses the chosen epiphanies (1 and 11) through the “translation kaleidoscope” and tries to achieve a critical comparison between different Polish translations. Analysing translations of the whole cycle, created by Maciej Słomczyński (James Joyce, Dzieła zebrane, vol.1, 1995) and Adam Poprawa (“Literatura na Świecie” 2007: 11–12) and searching for epiphanies hidden in Joyce’s great novels translated into Polish by different translators, the article presents The Epiphanies in various imensions, various interpretations and various spaces.
Wkład w przekład 2
Keywords: Epiphany in literature; James Joyce; Polish translations; Literary translation